Engineering a Biochemical Gradient in a 3D Small Intestinal Model with Topographical Features - Gee, Michelle M. (Tufts Archival Research Center, 2020)
The small intestine has microscale crypt and villus structures that create functional niches for proliferative cells in the crypts and differentiated cells on the villi. The localization of these cells is driven by a biochemical concentration gradient of factors. However, current in vitro intestinal models have been unable to combine this crypt and villus architecture with a biochemical gradient and the tubular 3D geometry of the small intestine. In this work, we utilized 3D printing to engineer a silk sponge scaffold mimicking the crypt and villus topography of the small intestine that supports the growth and differentiation of intestinal enteroids. The potential for biochemical gradients to be applied to this model is demonstrated using a silk sponge to release stem-maintaining factors. This approach combining 3D printing to engineer microscale structures in tissue scaffolds, biochemical cues, and a tubular 3D architecture serves as a model to facilitate the study of therapeutics, probiotics, and toxins. The methodologies used can be applied more generally to other tissue engineered organ systems with microscale structures and biochemical cues. Advisor: Dr. David Kaplan.